2008
DOI: 10.1177/1088357608323699
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Children With Autism Spectrum Disorders

Abstract: Balancing the roles of parent and partner is challenging for most people and may be especially challenging when extra time and effort are required in the parenting role. The current research compared 25 couples whose children have autism spectrum disorders (ASD) with 20 couples whose children do not have developmental disorders. Comparisons were made for both stressor (e.g., child's behavior problems) and relational (e.g., relationship satisfaction) variables. Results indicated that parents of children with AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
184
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 25 publications
8
184
1
9
Order By: Relevance
“…The increased chaos seen in families of children with ASD may also contribute to increased parental conflict and decreased marital satisfaction seen in these families (Brobst et al 2009;Gau et al 2011;Harper et al 2013;Hartley et al 2011). The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…The increased chaos seen in families of children with ASD may also contribute to increased parental conflict and decreased marital satisfaction seen in these families (Brobst et al 2009;Gau et al 2011;Harper et al 2013;Hartley et al 2011). The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…Roles of parents and partners are challenging for most people especially challenging when extra time and effort are required in the parenting role [31]. Numerous studies have shown that children with autism affect the relationship between other family members.…”
Section: Parent-child Relationshipmentioning
confidence: 99%
“…The authors reported that attachment was negatively impacted by the severity of autistic disorder symptoms. Similarly, Brobst and colleagues [31] conducted a study to examine the relationship between the child's behavioral problems and relationship satisfaction. In this study, interviews were conducted with 25 parents of children who have autistic disorder.…”
Section: Parent-child Relationshipmentioning
confidence: 99%
See 2 more Smart Citations